Dendrobium huoshanense C. Z. Tang & S. J. Cheng alleviates atherosclerosis by reducing lipid and improving vascular endothelial dysfunction - Fan, Xiang-Cheng; Cao, Wei-You; He, Min-Yang; Wang, Hui-Kai; Hao, Qing; Liu, Wen-Jing; Ren, Zhao-Ying; Wang, Li-Jun; Wang, Jing-Yu; Wang, Fei-Xue; Jiang, Lin; Zheng, Qiu-Sheng; et al. (Frontiers in Nutrition, 2025)
IntroductionDendrobium huoshanense C. Z. Tang & S. J. Cheng (DH) water extract has previously been found to have therapeutic effects on atherosclerosis (AS), but the active ingredients responsible for these effects remain unclear. This study aims to identify the active monomers in DH water extract that can treat AS, providing a basis for its use in preventing AS.MethodsLC-MS analysis was conducted to identify the main active ingredients in DH water extract. A zebrafish AS model was used to screen for the active ingredients with therapeutic effects. Network pharmacology was utilized to predict the mechanisms through which these active ingredients treat AS.ResultsSix main active ingredients were identified, and three, namely dendrophenol, naringenin, and apigenin-G, were selected for further study. Network pharmacology analysis indicated that naringenin and apigenin-G may treat AS by lowering blood lipid levels, including total cholesterol, triglycerides, low-density lipoprotein (LDL), and very low-density lipoprotein (VLDL), while dendrophenol may improve low shear stress (LSS)-induced endothelial cell dysfunction. Zebrafish model studies showed that naringenin and apigenin-G significantly reduced cholesterol, triglycerides, LDL, and VLDL levels. In the LSS-induced endothelial cell dysfunction model, dendrophenol significantly increased nitric oxide (NO) activity and reduced reactive oxygen species (ROS) activity.DiscussionThe findings suggest that DH may treat AS through the lipid-lowering effects of naringenin and apigenin-G, and by improving endothelial cell dysfunction via dendrophenol. Given that DH is a homology-of-medicine-and-food, it is suitable for preparation as a functional food aimed at preventing AS.